Characterization of quantum cascade lasers (II) - Lim, Natee Jing Xiang (Nanyang Technological University, 2024)
Quantum cascade lasers (QCL) were first introduced in 1994 and have quickly gained interest due to their high-power efficiency and output levels compared to regular lasers as well as their ability to emit within the terahertz range. Extensive research on QCLs has resulted in many articles on their properties and characteristics, the progress achieved since their development as well as their applications.